2020
DOI: 10.1053/j.gastro.2020.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopy Units and the Coronavirus Disease 2019 Outbreak: A Multicenter Experience From Italy

Abstract: U p to 20% of health care personnel (HCP) were found to be infected with coronavirus disease (COVID-19) 1 in the outbreak in northern Italy. 2 Recommendations on patient and HCP protection have been made, such as postponing procedures, triage, use of personal protective equipment (PPE), and creation of differentiated in-hospital pathways. 3,4 However, several barriers against the adoption of these strategies exist, including cultural factors and shortages of medical resources; therefore, there are few reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
113
2
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(133 citation statements)
references
References 1 publication
10
113
2
6
Order By: Relevance
“…Only two survey participants had examined patients with COVID-19 in an emergency situation. This is in contrast to the results of a survey from Italy in which about half of all endoscopy units were directly involved in emergent or urgent procedures in COVID-19 cases [13]. However, this may not have been the case in other parts of the world that did not experience the same extremely sharp rise in incidence of COVID-19 cases within a short period of time.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Only two survey participants had examined patients with COVID-19 in an emergency situation. This is in contrast to the results of a survey from Italy in which about half of all endoscopy units were directly involved in emergent or urgent procedures in COVID-19 cases [13]. However, this may not have been the case in other parts of the world that did not experience the same extremely sharp rise in incidence of COVID-19 cases within a short period of time.…”
Section: Discussioncontrasting
confidence: 83%
“…As with all other fields of medical practice, the COVID-19 pandemic has impacted gastrointestinal endoscopy, especially with regards to triage and prioritization of patients and procedures, cleaning and disinfection of equipment as well as protection of health care workers (HCW) [11,12]. A survey from northern Italy showed a dramatic burden of the pandemic on endoscopy units [13]. However, data on the effects of the pandemic on gastrointestinal endoscopy in central and sub-Saharan Africa (SSA) are lacking.…”
mentioning
confidence: 99%
“…Recently, another survey has been reported by Repici et al [18], conducted in high-risk areas of northern Italy. The coordinators of 41 endoscopic centers responded to the survey but individual endoscopists did not.…”
Section: Discussionmentioning
confidence: 98%
“…By early March, approximately 20 % of health care providers in Italy had been infected by SARS-Cov-2 [19]. In a survey conducted by Repici et al [18], 12 endoscopy units confirmed infections among nurses and physicians with six of them requiring hospitalization. However, there was no clear evidence of transmission directly related to endoscopic procedures in COVID-19-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Empfehlungsgrad: EL5/ Zustimmungsgrad: starker Konsens (98 %) Das Endoskopiepersonal ist über eine mögliche Inhalation von Tröpfchen und Aerosolen, Kontakt über die Konjunktiven sowie über den Stuhl einem erhöhten Risiko einer Infektion mit SARS-CoV-2 ausgesetzt. Eine vermehrte Transmission der Infektion in Krankenhäusern durch infizierte Mitarbeiter wurde beschrieben [77,78]. Endoskopien stellen einen Ort mit besonders hohem Übertragungsrisiko bakterieller und viraler Infektionen dar, sodass die Mitarbeiter dort in besonderer Weise geschützt werden sollten [79].…”
Section: Empfehlung 22unclassified